Sistem Pendukung Keputusan Pemilihan Masyarakat Penerima Bantuan Program Keluarga Harapan Metode SAW - Maria Yasinta Mau Rema; Yoseph D. Da Yen Khwuta; Elvira Esperanza Sala (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2022)
Uluwae II Village is one of the villages in the District on Nort Bajawa, Ngada Regency, whichis also a target village for receiving sicial assistance in the formof the Hope Program (PKH) assistance. PKH is a program of providing conditional social assistance to Beneficiary Families (PKM). In the particular, the objectives of PKH are to improve access and quality of education and health services for PKH participants, to in crease the education level of PKH participants, and to improve the health and nutritional status of PKH participants. Therefore, Uluwae II village official smust carefully select the right community to receive PKH assistance. In determining the PKH recipient community in Uluwae II village, it was still not right on targer, because the selection procces for the PKH recipient community was not running as expented by the community. Therefore, it is necessary to have a system to determine decision in determining the PKH recipient community. The purpose and benefit of this researchis to design and build decision support system to determine the right community to receive PKH according of the weigh to feach criterion. This research was completed through several stage, namely, collecting information through directre search at the location. The method used the SAW method to calculate the weight and determine the ranking.